2017
DOI: 10.1063/1.4990798
|View full text |Cite
|
Sign up to set email alerts
|

Scalable graphene aptasensors for drug quantification

Abstract: Simpler and more rapid approaches for therapeutic drug-level monitoring are highly desirable to enable use at the point-of-care. We have developed an all-electronic approach for detection of the HIV drug tenofovir based on scalable fabrication of arrays of graphene field-effect transistors (GFETs) functionalized with a commercially available DNA aptamer. The shift in the Dirac voltage of the GFETs varied systematically with the concentration of tenofovir in deionized water, with a detection limit less than 1 n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Using synthetic evolution of ligands through exponential enrichment (SELEX), we selected an aptamer with high affinity for azoles (9, 10). We also demonstrated that this aptamer could be successfully paired with the nascent technology of graphene field effect transistors (GFETs) to create electrical biosensors (11). We believe that this aptamer could be useful in many other sensing platforms.…”
Section: Observationmentioning
confidence: 99%
“…Using synthetic evolution of ligands through exponential enrichment (SELEX), we selected an aptamer with high affinity for azoles (9, 10). We also demonstrated that this aptamer could be successfully paired with the nascent technology of graphene field effect transistors (GFETs) to create electrical biosensors (11). We believe that this aptamer could be useful in many other sensing platforms.…”
Section: Observationmentioning
confidence: 99%
“…35 Specifically, their smaller size reduces the Debye screening effect, producing high sensitivity (∼ pg/ml) for the detection of proteins utilizing DNA aptamer probes. [36][37][38] Also, the strongly charged backbone of aptamers results in significant changes in the charge carrier density in the graphene channel upon folding or unfolding during target binding.…”
Section: Introductionmentioning
confidence: 99%
“…After confirming the aptamers’ functionalization on G‐FETs, we turned to investigate and maximize the sensitivity of the devices to CA1. The sensitivity of G‐FET based aptameric biosensors relies on the amount of shift in V D resulting from electrostatic charges induced upon binding of aptamers with target analytes (Saltzgaber et al, 2013; Vishnubhotla et al, 2017). Thus, the charges associated with different biomarkers and their distance from the graphene surface could significantly affect the sensitivity of such sensors.…”
Section: Resultsmentioning
confidence: 99%
“…The small size, easy synthesis and high stability make apatmer probes particularly advantageous for incorporation into G‐FET devices (Cai et al, 2018). Specifically, their smaller size reduces the Debye screening effect, producing high sensitivity (~pg/ml) for the detection of proteins utilizing DNA aptamer probes (Saltzgaber et al, 2013; Vishnubhotla et al, 2017; Wang, et al, 2016). Also, the strongly charged backbone of aptamers results in significant changes in the charge carrier density in the graphene channel upon folding or unfolding during target binding.…”
Section: Introductionmentioning
confidence: 99%